P539 Patient Preferences for Inflammatory Bowel Disease Treatments: Development of a European Preference Survey using a Discrete Choice Experiment. (30th January 2023) - Schoefs, E; Vermeire, S; Ferrante, M; Sabino, J; Verstockt, B; Avedano, L; De Rocchis, M S; Sajak-Szczerba, M; Saldaña, R; Straetemans, N; Vandebroek, M; Huys, I; et al.
Abstract: Background: There is a growing consensus across stakeholders on the value of patient preference (PP) studies, as recognized by the European Medicines Agency and the European Network for Health Technology Assessment. This study aimed to develop a PP survey to quantitatively evaluate which characteristics are most important to inflammatory bowel disease (IBD) patients, so that the results can inform the medicinal product life cycle (MPLC). Methods: Following the PREFER recommendations, a four-step approach was followed to develop the PP survey: 1) stated preference method selection, 2) attribute and level development, 3) survey implementation, and 4) survey piloting. Throughout the different steps of the survey development, an advisory board (AB) consisting out of patients, patient organizations, gastroenterologists, IBD nurses, and statisticians were consulted. Results: First, a discrete choice experiment (DCE) was chosen as the preferred elicitation method because it allows to reach the objectives of the survey, namely to: 1) quantify the relative importance of different attributes, 2) elicit the trade-offs patients make, and 3) measure preference heterogeneity. Second, a scoping literature review of IBD clinical trials, available IBD treatments, and previously published preference studies was performed. Discussions on these characteristics with patients (n=11) during focus group discussions (FGDs) using the nominal group technique revealed the following patient prioritized characteristics: prevent surgery, long-term clinical remission, improved quality of life, occurrence of urgency, and improved labor rate. Based upon the results of the FGDs, a preliminary list of possible attributes for inclusion in the DCE was refined during AB meetings. This list was iteratively adapted until consensus was found on 14 attributes, their levels, and corresponding explanations (Figure 1). Third, the DCE survey was designed to include these 14 attributes using partial profiles next to measures about sociodemographic variables, health literacy, and treatment experience. Fourth, piloting the study with IBD patients (n=4) revealed that the survey was comprehensible, had a good flow, and contained graphics that supported the content. Only minor text edits were needed. Conclusion: It is key to develop a PP survey in partnership with patients and other members of the AB. This survey will be rolled out across Europe in 11 different languages and will increase understanding of which treatment aspects are most important to IBD patients. These aspects should be included in drug development and evaluation so that the MPLC can be more patient-centered and future treatments will target aspects that are most important to IBD patients themselves.